Managing Stress During the Coronavirus Among Students from Technical Specialization: A Case Study of Several Universities in Romania - Loredana C. DUMITRIU; Marian COSAC; Gheorghe SOLOMON (Communications of International Proceedings, 2022)
COVID-19 pandemic affected everyone around the globe. Countries worldwide implemented strict precautions on education systems and many students experience stress related to changes in lifestyle and online classes.  As we know, the COVID-19 pandemic affects the society emotionally, psychologically and socially, not just medically. This study was undertaken in several universities from Romania and the survey was opened online between March 2020 to January 2021. The purpose of this paper is to detect stress during the lockdown among the students from technical specialization. From literature, in order to perceived stress scale by students, it has been used Cohen’s Perceived Stress Scale because it has shown good reliability in various studies. The demographic data related a total of 1300 respondents who took part in this case study, from the academic environment, aged 19 to 26; 836 of them were female and 464 males. The respondents came from universities situated in cities such as: Bucharest, Craiova, Cluj-Napoca, Iași, Ploiesti, Timișoara, Brasov and Oradea. The model has been realized taking into consideration various factors that contributed to the stress experience in online education, such as academic, social and psychological factors. This research showed that the higher stress among university students was connected to their lower academic performances comparing to the ones pre-pandemic. Over the time, many studies took place, but this article will be a highlighted one in the awareness of the need to implement training in stress management among students, to help them overcome the COVID situation from all points of view.
Keywords: stress; students; COVID-19; questionnaire